Answer:
Hey! The answer would be 63.
Explanation:
First, you have to simplify both sides of the equation.
Next, add 9 to both sides.
And finally, multiply both sides by 3.
following these steps will leave you to the answer:
Y= 63
hope this helps!
63
so y/3 - 9 = 12, add 9 on both sides and you get y/3 = 21. Then you multiply both sides by 3, y/3 * 3, the 3's cancel out, 21 * 3 = 63. You get y = 63
So basically just do + 9 on both sides then *3 on both sides (do it step by step)
5.8m questions
7.5m answers